The Effect of Self-Efficacy on Mathematical Critical Thinking of Special Needs Students - Danuri Danuri; Kurnia Pawestri Primastuti; Nuryadi Nuryadi (MASI Mandiri Edukasi, 2026)
Inclusive education provides equal learning opportunities for students with special needs; however, developing higher-order thinking skills, particularly critical thinking in mathematics, remains a challenge. Self-efficacy is considered an important psychological factor that can influence students' learning outcomes and critical thinking skills. However, previous studies have reported inconsistent findings regarding the relationship between self-efficacy and critical thinking in mathematics, especially among students with special needs in inclusive elementary schools. Therefore, this study aims to analyze the influence of self-efficacy on critical thinking skills in mathematics of fourth-grade students with special needs in inclusive elementary schools in the Pangeran Diponegoro Cluster, Purworejo Regency. This study used a quantitative survey research design. Participants were 22 fourth-grade students with special needs, selected through total sampling. Data were collected using a self-efficacy questionnaire and a critical thinking test in mathematics. The validity and reliability of the instruments were confirmed prior to data collection. Data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, and the Spearman rank correlation test. The findings indicate that most students exhibit moderate levels of self-efficacy (77%), while their critical thinking skills in mathematics tend to be low (32%). Spearman Rank analysis showed a weak positive correlation between self-efficacy and critical thinking skills in mathematics (r = 0.318), but the relationship was not statistically significant (p = 0.149). This study concludes that self-efficacy does not significantly influence students with special needs' critical thinking skills in mathematics. Critical thinking skills in mathematics appear to be influenced by a range of cognitive, motivational, and environmental factors beyond self-efficacy alone. This study contributes to the literature on inclusive education by providing empirical evidence regarding the relationship between self-efficacy and critical thinking skills in mathematics among students with special needs. In practice, the findings suggest that teachers should collaborate to improve students' self-efficacy through instructional strategies that foster critical thinking, such as problem-based learning, differentiated instruction, and metacognitive approaches.